A New Blasting Permeability Enhancement Scheme For Deep-Buried Soft Coal Mining Face Based on Borehole Deformation Characteristics - Xuan, Dequan; Zhang, Jianhua; Huang, Gang; Li, Peng; Zhang, Zhifeng (Frontiers in Earth Science, 2022)
When blasting to enhance permeability in deep buried soft coal mining face with hard roof whose gas drainage requirement is higher, the charging hole and control hole (doubles as drainage hole) are easy to be deformed and damaged, seriously affecting the blasting implementation and effect.Combining with the stratum characteristics of soft coal seam and hard surrounding rock, the idea of arranging boreholes near the surrounding rock to reduce deformation, inspired by end effect, is put forward.Then,the experimental research on the deformation characteristics of boreholes at different distances from the surrounding rock is carried out,and the results show that the closer the borehole is to the roof (floor) , the smaller the deformation, under the same stress conditions and within a certain distance.Based on this, a new scheme of arranging control holes and blasting holes near the roof and floor is proposed and designed. The field test results show that the blasting of 60m deep holes are successfully realized and the remarkable permeability enhancement effect is achieved, verifying the feasibility and effectiveness of the scheme.This study explores a new blasting permeability enhancement scheme with practical value and reference significance for deep buried soft coal mining face with hard roof.